Penyimpangan Prinsip Kerja Sama dalam Penciptaan Humor Wacana Lisan Stand-Up Comedy Ali Akbar: Kajian Pragmatik - Fadillah, Reza Bakti; Suparwa, I Nyoman; Simpen, I Wayan (CV. Ulil Albab Corp, 2024)
This research is entitled “Deviation of the Principle of Cooperation in the Creation of Humor in Ali Akbar's Stand-Up Comedy Oral Discourse: A Pragmatic Study”. There are two problems in this research, namely what deviations of the principle of cooperation are contained in the oral discourse of Ali Akbar's stand-up comedy, and what kind of humor is contained in the oral discourse of Ali Akbar's stand-up comedy. This study aims to classify the form of deviation of the principle of cooperation used as a means of creating humor contained in the oral discourse of Ali Akbar's stand-up comedy. The theory used in this study is the theory of the principle of cooperation Grice in Wijana (1996). The data collection method used is the listening method equipped with the tapping technique and the advanced technique of free listening and speaking and the note-taking technique. The data analysis method is the matching method and the distribution method. The method of presenting the results of the data analysis used in this study is the informal method. Based on the analysis that has been carried out, the form of deviation of the principle of cooperation is found to include, deviation of single maxims and deviation of double maxims. The humor contained is joking, insulting, complaining, and satirizing.